Devaluation of Family and Human Behaviour in Sudha Murty’s House of Cards - N. Sabthami; Dr. D. Shanmugam (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The research paper entitled “Devaluation of Family and Human Behaviour in Sudha Murty’s House of Cards aims to explore the tendency of human relationship. Sudha Murty is one of the most realistic woman writers in India who strongly clutches the values throughout her writings. She penned the characters in an elegant way. In the novel House of Cards, Murty expresses how the family system gets disturbed due to urban life. This paper analyses the family dysfunction owing to several changes in humanistic values. When the people start migrating from rural areas to urban areas in search of their livelihood, they adapt the changes in their life style as well as their behaviour. The author pictures the struggles faced by the common people through the protagonists Sanjay and Mridula. When Sanjay admires materialistic life, he loses his moral values and becomes a victim of social injustice. But Mridula never changes her beliefs and behaviours. There are some people who adopt themselves to the urban life and some get changed in their behavioural pattern. It is Mridula gets adopted to the changes, but stays constant and Sanjay gets changed in his characters and values. It is a heartwarming story of a woman’s journey towards empowerment and independence, and the obstacles that she overcome along the way.